2008
DOI: 10.3325/cmj.2008.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 and p27 Expression as Prognostic Factor in Papillary Carcinoma of the Thyroid: Association with Clinicopathological Parameters

Abstract: Aim To determine the prognostic value of cell cycle regulators cyclin D1 and p27 for papillary thyroid carcinomas.Methods Analysis included 180 patients with papillary thyroid carcinoma who underwent surgery at Split University Hospital Center between 1999 and 2001. Clinical data were obtained from clinical charts and histopathology reports. Immunohistochemistry was performed on formalin-fixed, paraffin-embedded tissue by antibody p27 and cyclin D1. Quantification was based on the intensity and distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
(26 reference statements)
3
23
1
2
Order By: Relevance
“…All of the tumors chosen for this study were cyclin D1 positive and these results are consistent with a previous study conducted by Saiz et al 19 Overexpression of cyclin D1 has been identified as a predictor of lymph node metastasis in papillary thyroid carcinoma; 7,8,10 however, we found no significant correlation between its overexpression (more than 25% of positively staining tumor cells) and lymph node metastasis (P ¼ 0.061). The isolated glands, which are defined as individual glands of papillary thyroid carcinoma cells found in the extra-tumoral region, are distinctive histological features of papillary thyroid carcinoma and should not be confused with the tumor multifocal foci.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…All of the tumors chosen for this study were cyclin D1 positive and these results are consistent with a previous study conducted by Saiz et al 19 Overexpression of cyclin D1 has been identified as a predictor of lymph node metastasis in papillary thyroid carcinoma; 7,8,10 however, we found no significant correlation between its overexpression (more than 25% of positively staining tumor cells) and lymph node metastasis (P ¼ 0.061). The isolated glands, which are defined as individual glands of papillary thyroid carcinoma cells found in the extra-tumoral region, are distinctive histological features of papillary thyroid carcinoma and should not be confused with the tumor multifocal foci.…”
Section: Discussionsupporting
confidence: 67%
“…In some studies, cyclin D1 expression was not an independent predictive factor for lymph node metastasis during multivariate analysis, although it has been found to be associated with lymph node metastasis in univariate analysis. 10,11 BRAF V600E mutation has frequently been detected in papillary thyroid carcinoma, but has not been identified in benign thyroid lesions. 12,13 In Korea, the prevalence of the BRAF V600E mutation accounts for up to 87% of all cases of papillary thyroid carcinoma.…”
mentioning
confidence: 99%
“…PTCs with increased cyclin D1 and decreased p27 expression have been linked to metastatic nodal disease [25][26][27][28][29]. In a previous study, HBME-1 expression has been linked to the prediction of lymph node metastasis even within the RASlike PTCs [29].…”
Section: Discussionmentioning
confidence: 97%
“…Cyclin-D1 in tumors was labeled as negative if <10%, moderately positive between 10% and 50%, and strongly positive if >50%, tumor cells expressed the antigen. [7,8] Assessment of tumor response was done by clinical examination, radiologic investigations (computed tomography [CT]-scan) 4-6 weeks after completion of treatment. Biopsy or fine needle aspiration cytology to determine pathologic response was not performed routinely; it was done only in case of partial response (PR)/suspected lesion to confirm the presence of disease.…”
Section: Methodsmentioning
confidence: 99%